KELAYAKAN MEDIA PEMBELAJARAN (BOOKLET) PADA SUBMATERI KONSEP PERTUMBUHAN DAN PEMBANGUNAN EKONOMI KELAS XI DI SMA NEGERI 1 SENGAH TEMILA - Nela, Nela; Warneri, Warneri; Syamsuri, Syamsuri (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2023)
Learning media is a means to convey the contents of the material, making it easier for teachers to convey the contents of the subject matter, making it easier for teachers to convey messages or to students. One model of learning media is a learning resource that contains material, as well as pictures related to the material that will be delivered by the teacher, with this media it can help students understand the material in an easy way and can attract students' interest. One of the learning media used is booklet media where a booklet is a book that has a minimum of 5 pages but no more than 48 pages on the cover count. This study aims to determine the feasibility of media booklets in the sub-matter of economic growth and development and to determine students' perceptions of media booklets in class XI SMA Negeri 1 Sengah Temila. The research method used is descriptive analysis method in qualitative research and the data collection technique used is interviews. The results showed that the booklet learning media made for the material on the concept of economic growth and development at SMA Negeri 1 Sengah Temila is appropriate for use in the learning process.